Travel and Education - Vuk Trnavac (Etnoantropološki Problemi)
"What we talk about when we talk about travel: A contribution to the critique of the teleology of education", Predrag Krstić and Aleksandar Ostojić, Institute for Philosophy and Social Theory, Belgrade, 2023.